Uniform Attractor for the Fractional Nonautonomous Long-Short Wave Equations. (19th October 2014) - Ge, Huanmin; Xin, Jie
Abstract : We firstly proved the existence and the uniqueness of the solution for the 2 π -periodic fractional nonautonomous long-short wave equations with translation compact force by using Galerkin method and then obtained the compact uniform attractor of the system.